2018
DOI: 10.4103/lungindia.lungindia_405_17
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric inflammatory myofibroblastic tumor of the trachea: Imaging spectrum and review of literature

Abstract: Inflammatory myofibroblastic tumor of the airway is a very uncommon benign primary neoplasm in pediatric age group with increased local recurrence rate and potential metastatic spread. We describe a case of a 6-year boy who was brought to the pediatric emergency with severe respiratory distress, dry cough, and stridor. Contrast-enhanced computed tomography and magnetic resonance imaging (MRI) of the neck showed a polypoidal mass lesion in the right anterolateral trachea causing significant airway narrowing. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Bronchoscopy and transbronchoscopic biopsy are necessary for the evaluation, diagnosis and treatment of airway obstructive injury (25)(26). Studies have found that the diagnosis of IMT is mainly determined by histopathology and immunohistochemical examination through biopsy (13)(14)(15)(16)(17)(18)(19)(20)(21). The pathological manifestations of IMT are as follows: [1] A large number of proliferating spindle cells are arranged in bundles; [2] The nuclei may be slightly heteromorphic, with mitotic images occasionally seen; [3] Lack of pathological mitosis and coagulation necrosis; [4] A mixture of spindle cells, lymphocytes, plasma cells and eosinophils existed (2,27).…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy and transbronchoscopic biopsy are necessary for the evaluation, diagnosis and treatment of airway obstructive injury (25)(26). Studies have found that the diagnosis of IMT is mainly determined by histopathology and immunohistochemical examination through biopsy (13)(14)(15)(16)(17)(18)(19)(20)(21). The pathological manifestations of IMT are as follows: [1] A large number of proliferating spindle cells are arranged in bundles; [2] The nuclei may be slightly heteromorphic, with mitotic images occasionally seen; [3] Lack of pathological mitosis and coagulation necrosis; [4] A mixture of spindle cells, lymphocytes, plasma cells and eosinophils existed (2,27).…”
Section: Discussionmentioning
confidence: 99%